Implementasi Teknik Compositing Film Animasi Hybrid “Tingkuluak: Pusaka Perempuan Minang dalam Sehelai Kain" - Muhammad Dyosa Rifqi; Sheanny Ocmi Sakti (YASIN, 2026)
Although the use of hybrid animation to convey cultural values continues to develop, studies on the application of compositing that integrates visual and audio elements in Tingkuluak-themed animated films remain limited. This study aimed to describe the implementation of compositing techniques in the hybrid animated film “Tingkuluak: Pusaka Perempuan Minang dalam Sehelai Kain” and assess their contribution to audiovisual unity. The study employed a qualitative descriptive approach with a design-based practice and animation pipeline design. Data were collected through online questionnaires administered to adolescents, school students, and university students, an interview with one key informant, a literature review, production documentation, alpha testing, and beta testing by animation experts. The data were analyzed descriptively and thematically. The results showed that compositing techniques were able to integrate 2D and 3D animation, motion graphics, voice-over, sound effects, background music, and simple visual effects through layer arrangement, color grading, audio processing, and audiovisual integration. The testing results identified three technical aspects requiring improvement, namely visual composition, transitions, and lighting, as well as five expert recommendations covering title design, subtitles, text animation, color consistency, and character expressions. These findings confirm that compositing serves as both a technical and creative stage in establishing audiovisual unity and supporting the communicative delivery of Minangkabau cultural messages.